Towards More Objective Teaching Curriculum Design and Development - Hatem, Hikmat Abdel Rassiul (AL-Kindy College Medical Journal, 2010)
have been notable developments in the field ofr.ldical education in the country and in the region.The most significant of which is a general awarnessthat has been created about the need for andrelevance of changes.There is however a basicquestion that posses itself and becomes clearlyrelevantin the context of effort .Today, to recognize healthcare services in the developing countries in the lightof realigned priorities This ensure to bring aboutlearning outcomes as a tocurriculum changes to meetthis demand.